The usage of derivatives and firm market value : An empirical study on Finnish listed firms 2014–2018 - Slavic, Jani-Áron (My University, 2019)
Derivatives are widely utilized in corporate level risk management in order to hedge market risks, such as foreign currency risk, interest rate risk and fluctuations in commodity prices. Derivatives have experienced increasing regulation following the 2007–2008 financial crisis. This has led to questioning the value of derivatives as a part of corporate risk management strategy. In March 2016 the ECB for the first time ever reduced its main refinancing rate to 0 % while almost simultaneously for the first time ever the 12 months Euribor rate turned negative. This was preceded and succeeded by a general decline in the level of interest rates for a few years following the financial crisis and the ensuing eurozone debt crisis. This development also questions the efficiency of particularly interest rate derivatives as a part of corporate hedging practices in the eurozone. According to the theory of independence between capital structure and firm market value, risk management should not affect firm market value. However, according to the positive corporate risk management theory, firms may increase their market value by reducing cash flow volatility with derivatives. This thesis studies the relation between hedging and firm market value proxied by Tobin’s Q in firms listed in the NASDAQ OMX Helsinki stock exchange between years 2014 and 2018, emphasizing the negative interest rate environment. In total 537 firm-year observations are analyzed. In univariate and multivariate tests hedgers are divided into foreign currency, commodity price and interest rate hedger groups. Student’s t-tests and Wilcoxon-Mann-Whitney tests are utilized to measure the premia separately for positive and negative interest rates’ periods. In pooled ordinary least squares regressions multiple control variables are considered. Also, the firm value effects of scaled firms’ nominal hedging positions are tested via utilizing hedging coverage as a previously minimally tested additional control variable. The overall results contrast with most of the prior research. The results from univariate tests indicate the existence of significant negative value premia for all hedger types during the whole sample period. Multivariate test results, considering control variables, confirm the existence of negative value premia for general hedgers. The hedging coverage control variable is significant and negative only for interest rate hedgers. Moreover, the overall results of the thesis are largely driven by interest rate hedgers. Further research with a larger international sample throughout especially the negative interest rates’ era for interest rate hedgers, considering hedging coverage, is needed to confirm the results as the samples of hedgers in this thesis overlap.
Keywords: derivatives, risk management, hedging, firm market value, johdannaiset, riskinhallinta, suojautuminen, yritysarvo